(untitled) (ModaPalavra e-periódico, 2014)
Bibliographical study on the relationship between the costume, historical research and the relationship between the wear and the conditions of gender identity and social group. From relevant literature survey is touted as the suit arises throughout human history as an important factor of social and cultural demarcation.